From strategy to action: leveraging transformative levers to support Africa's fertilizer and soil health strategy - Frank Rasche; Bernard Vanlauwe (Soil Security, 2025)
Africa’s vast arable land offers immense agricultural potential, yet productivity remains constrained by climate change, soil degradation, limited technology adoption, and socio-economic barriers. This has created the need for transformative change in the agricultural sector, with soil health playing a key role in this transition. Soil health is essential for agricultural productivity, economic viability, and ecosystem resilience, while also advancing sustainability and inclusivity. Achieving these outcomes depends on effective soil management, but slow growth in fertilizer use and limited understanding of its efficiency by farmers pose significant challenges. The Africa Fertilizer and Soil Health Summit (Nairobi, May 2024) underscored the urgency of these challenges, endorsing the African Fertilizer and Soil Health Action Plan. This commentary outlines key considerations for successful implementation of the plan, highlighting enabling conditions and strategic approaches: (1) trusted multi-sectoral partnerships fostering collaboration among farmers, governments, private companies, non-governmental organisations, and donors, (2) demand-driven research and development with strong focus on measurable development outcomes, (3) targeted investments and finance effectively expanding the role of the private sector, (4) effective policy mandates relying on comprehensive policy mixes, and (5) inclusive capacity-building using gender-transformative approaches. These strategic contributions are essential to achieving sustainable, equitable agricultural transformation in Africa. The transformation will demand innovation, long-term commitment, and coordinated action across sectors to ensure impact beyond the timeframe of the African Fertilizer and Soil Health Action Plan.